A Novel Strategy Achieving GaN Ultra-Smooth Surface via a Square, Flat Top Beam Shaped Femtosecond Laser Processing Combined with Chemical Mechanical Polishing. (1st May 2022) - Chen, Gaopan; Peng, Qingfa; Long, Jiangyou; Luo, Haimei; Zhou, Yan; Xie, Xiaozhu; Pan, Guoshun; Wang, Xiaofeng
Abstract : We propose a strategy for GaN ultra-smooth manufacture by combing of femtosecond laser processing and chemical mechanical polishing. The optimized flat top beam is used to redistribute the laser fluence from Gaussian distribution to square, flat top profile. Surface with high flatness is achieved after femtosecond laser processing through optimization of the technical parameters. The optimum process to control the damages on surface and subsurface reduces negative influence of femtosecond laser processing on chemical mechanical polishing. Roughness ( Ra ) of processed surface is decreased to less than 0.1 nm when it is be polished for 6 h. In the background of traditional GaN polishing efficiency facing bottleneck, the characteristic of present study is to use a square, flat top beam shaped femtosecond laser to induce surface of GaN. Structures and composition on induced surface are simultaneous removed in chemical mechanical polishing process. It reduces the burden of GaN chemical mechanical polishing. The present method has advantage of high efficiency and easy realization, which has a wide application in GaN ultra-smooth processing.